Multivariate Statistical Approach in Modeling Surface and Groundwater Quality near Municipal Solid Waste Dump Sites in Warri Metropolitan City - Mamuyovwi Odia; Ify L. Nwaogazie (Archives of Current Research International, 2017)
Water sources are usually polluted by waste generated by human activities. This work examined the activities on three dump sites on surface and groundwater quality in Warri metropolis. Water samples from boreholes, dug-wells and stream sources around Niger-Cat, Don-Parkar and Orhuwhorun dump sites were assessed for their water quality. Purposive sampling technique was employed in the collection of water samples for the sampling period of September, November and January and the concentration of water quality parameters were determined. Principal Component Analysis (PCA) and Multiple Linear Regression (MLR) were applied to simulate Water Quality Index (WQI) models for the monitoring and prediction of water quality of groundwater and surface water around the dump sites. The models yielded goodness of fit (R2) values which ranged from 0.9997 to 0.9999 (99%). The modeled WQI values for Boreholes: BH1, BH2 and BH3 were 60.9, 8.2 and 41.8, while Dug-wells: DW1, DW2 and DW3 were 208.2, 49.3 and 51.5 at Niger-Cat. BH1, BH2 and BH3 were 15.5, 30.8 and 36.6, while DW1 and DW2 were 30.2 and 38.4 for Don-Parkar. For Orhuwhorun dump site, BH1 and BH2 were 33.5 and 16.2; DW1, DW2 and DW3 were 49.7, 40.4 and 21.4, while Stream SM1 was 8.7. Findings revealed that waters of the three dump sites were acidic and the quality ranged from excellent quality to unsuitable for drinking.